Acid-Sensing Ion Channel 1/Calpain1 Activation Impedes Macrophage ATP-Binding Cassette Protein A1-Mediated Cholesterol Efflux Induced by Extracellular Acidification - Wang, Yuan-Mei; Tan, Mo-Ye; Zhang, Rong-Jie; Qiu, Ming-Yue; Fu, You-Sheng; Xie, Xue-Jiao; Gu, Hong-Feng (Frontiers in Physiology, 2022)
Background: Extracellular acidification is a common feature of atherosclerotic lesions, and such an acidic microenvironment impedes ATP-binding cassette transporter A1 (ABCA1) -mediated cholesterol efflux and promotes atherogenesis. However, the underlying mechanism is still unclear. Acid-sensing ion channel 1 (ASIC1) is a critical H+ receptor, which is responsible for the perception and transduction of extracellular acidity signals. Aim: Here we explored whether or how ASIC1 influences extracellular acidification-induced ABCA1-mediated cholesterol efflux from macrophage-derived foam cells. Methods: RAW264.7 macrophages were cultured in an acidic medium (pH 6.5) to generate foam cell. Then intracellular lipid deposition, cholesterol efflux, and ASIC1/calpain1/ABCA1 expressions were evaluated. Results: We showed that extracellular acidity enhanced ASIC1 expression and translocation, promoted calpain1 expression and lipid accumulation, and deceased ABCA1 protein expression as well as ABCA1-midiated cholesterol efflux. Of note, inhibiting ASIC1 activation with amiloride or Psalmotoxin 1 (PcTx-1) not only lowered calpain1 protein level and lipid accumulation, but also enhanced ABCA1 protein levels and ABCA1-mediated cholesterol efflux of macrophages under extracellular acidity conditions. Furthermore, similar results were observed in macrophages treated with calpain1 inhibitor PD150606. Conclusion: Extracellular acidification declines cholesterol efflux via activating ASIC1 to promote calpain1-mediated ABCA1 degradation. Thus, ASIC1 may be a novel therapeutic target for atherosclerosis.